Modeling the health and economic implications of adopting a 1-dose 9-valent human papillomavirus vaccination program in adolescents in low/middle-income countries: An analysis of Indonesia. - Vincent Daniels; Kunal Saxena; Oscar Patterson-Lomba; Andres Gomez-Lievano; Jarir At Thobari; Nancy Durand; Evan Myers (PLoS ONE)
Background Recent evidence suggests that 1 dose of the human papillomavirus (HPV) vaccine may have similar effectiveness in reducing HPV infection risk compared to 2 or 3 doses. Objective To evaluate the public health impact and cost-effectiveness of implementing a 1-dose or a 2-dose program of the 9-valent HPV vaccine in a low- and middle-income country (LMIC). Methods We adapted a dynamic transmission model to the Indonesia setting, and conducted a probabilistic sensitivity analysis using distributions reflecting the uncertainty in levels and durability of protection of a 1-dose that were estimated under a Bayesian framework incorporating 3-year vaccine efficacy data from the KEN SHE trial (base-case) and 10 year effectiveness data from the India IARC study (alternative analysis). Scenarios included different coverage levels targeted at girls-only, or girls and boys. Costs and benefits were computed over 100 years from a national single-payer perspective. Results Depending on the coverage and target population, the median number of cancer cases avoided in 2-dose programs ranged between 600,000-2,100,000, compared to 200,000-600,000 in 1-dose programs. The 1-dose programs are unlikely to be cost-effective compared to 2-dose programs even at low willingness-to-pay (WTP) thresholds. The girls-only 2-dose program tends to be cost-effective at lower WTP thresholds, particularly in scenarios with high coverage, dose price and discount rate, while the girls and boys 2-dose program is cost-effective at higher WTP thresholds. In the alternative analysis, 1-dose programs have higher probability of being cost-effective compared to the base-case, particularly for low WTP thresholds (less than 0.5 GDP) and for high coverage, dose price and discount rate. Conclusion Adoption of 1-dose programs with 9-valent vaccine in an LMIC resulted in more vaccine-preventable HPV-related cancer cases than 2-dose programs. The 2-dose programs were more likely to be cost-effective than 1-dose programs for a wide range of WTP thresholds and scenarios.